Electrically driven strain-induced deterministic single-photon emitters in a van der Waals heterostructure - So, Jae-Pil; Kim, Ha-Reem; Baek, Hyeonjun; Jeong, Kwang-Yong; Lee, Hoo-Cheol; Huh, Woong; Kim, Yoon Seok; Watanabe, Kenji; Taniguchi, Takashi; Kim, Jungkil; Lee, Chul-Ho; Park, Hong-Gyu (AMER ASSOC ADVANCEMENT SCIENCE, 2021)
Quantum confinement in transition metal dichalcogenides (TMDCs) enables the realization of deterministic single-photon emitters. The position and polarization control of single photons have been achieved via local strain engineering using nanostructures. However, most existing TMDC-based emitters are operated by optical pumping, while the emission sites in electrically pumped emitters are uncontrolled. Here, we demonstrate electrically driven single-photon emitters located at the positions where strains are induced by atomic force microscope indentation on a van der Waals heterostructure consisting of graphene, hexagonal boron nitride, and tungsten diselenide. The optical, electrical, and mechanical properties induced by the local strain gradient were systematically analyzed. The emission at the indentation sites exhibits photon antibunching behavior with a g((2))(0) value of similar to 0.3, intensity saturation, and a linearly cross-polarized doublet, at 4 kelvin. This robust spatial control of electrically driven single-photon emitters will pave the way for the practical implementation of integrated quantum light sources.